Teacher of Physical Education Pedagogical Culture (Eurasian Journal of Learning and Academic Teaching, 2022)
this article covers the pedagogical culture of the teacher of the science of Physical Culture, the structure and content of the bakalavri culture of Physical Culture, the special abilities and peculiarities of the pedagogical person